The effectiveness of alluvial gully remediation in Great Barrier Reef catchments - Andrew P. Brooks; John Spencer; Nicholas J.C. Doriean; Robin Thwaites; James Daley; Tim Pietsch; Jorg Hacker; Justin Stout (International Soil and Water Conservation Research)
This study presents data from a large-scale Before After Control Impact (BACI) design field experiment that measured the sediment reduction achieved by remediating large alluvial gullies. The study was carried out on Bonnie Doon Creek on the lower Burdekin River, in Queensland Australia. Prior to remediation, the four large alluvial gully complexes (active area of ∼17ha) were conservatively estimated to be delivering 5800 ± 1500 t of fine sediment (<20 μm) per year (20 year average). The experiment demonstrated that the average remediation effectiveness across 10 different treatments was a 96%–99% reduction in fine sediment yield (or an annualised reduction of ∼5500t). High resolution lidar DEM of Difference (DoD) derived sediment yields in the unremediated gullies were found to be, on average, 58% lower than yields derived from monitored suspended sediment concentration (SSC) data, albeit with some uncertainty. These data support the notion that even high resolution (0.1m) lidar DoD yields are missing erosion driven by rainfall driven downwearing across all internal gully surfaces that is below the limit of detection (LOD) of the lidar. The results highlight that the greatest uncertainty in predicting the sediment abatement from gully remediation is associated with the determination of the baseline sediment yield of each gully. Future research effort should be focused on improving our understanding of baseline (multi-decadal) sediment yields, and monitored (annual) yields in different types of unremediated gullies. This is dependent on developing a detailed understanding of how these gullies evolve through time, and what the processes are that drive ongoing gully growth.